GANGGUAN BERBAHASA AFASIA MOTORIK PADA PENDERITA GANGGUAN TUMOR KEPALA PADA USIA DEWASA - Ahmad Drani (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2020)
Abstract  The purpose of this study is to describe language disorders (motor aphasia). The details of the purpose of the study are to describe language disorders (Motor Aphasia), to describe the causes of language disorders (Motor Aphasia), to describe how the use of language in people with language disorders (Motor Aphasia). The research method used in this study is a qualitative method. The results of this study indicate that 56-year-old aphasia sufferers who are the subjects of this study can tell news, question, command, and single sentence sentences. Aphasia patients aged 56 years in general are able to speak sentences in the pattern of SP, PS, PK. KeyWords: Interference, Language, Aphasia